First records of Epimeriidae and Iphimediidae (Crustacea, Amphipoda) from Macquarie Ridge, with description of a new species and its juveniles - Lörz, Anne-Nina (Zootaxa, 2012)
Amphipod species of the families Epimeriidae and Iphimediidae are recorded for the first time from Macquarie Ridge, asparsely sampled mid-ocean ridge between New Zealand and Antarctica. Epimeria ashleyi sp. nov. collected from twoseamounts on the Macquarie Ridge between 676–1025 m water depth is described in detail.Epimeria ashleyi sp. nov. can be distinguished from similar species by the unique combination of following charac-ters: pointed coxa 1–3, dorsal doublecarinae as well as three lateral projections on epimeral plates 1–3. The juveniles ofthe new species are described and are considerably different from the adults. Additionally, Labriphimedia pulchridentata(Stebbing, 1888), previously known only from Heard Island, is recorded from Macquarie Ridge seamounts with first images of its colour in life.